Electrochemical preparation of Al- Li alloy from Urea-LiCl molten salt at 353–393 K - Gao, Bingliang; Liu, Zhiwei; Deng, Yifan (Frontiers in Chemistry, 2023)
Al-Li alloy was prepared by electrodeposition on solid aluminum electrode in a urea-LiCl (77.5:22.5, mol%) molten salt system at 353–393 K. The results of cyclic voltammetry and chronopotentiometry show that underpotential deposition of Li occurs on the Al electrode and forms phases of Al(α) and AlLi(δ) which are confirmed by XRD measurements. Scanning electron microscopy observation of deposits indicates that Al-Li alloy with the thickness of 143 µm was obtained by potentiostatic electrolysis at −0.5 V vs. Li+/Li. The Li content in the alloy obtained at 373 K can reach 6.9 wt%. Galvanostatic electrolysis at 20 A demonstrated that Al-Li alloy coating on aluminum plate can be obtained from urea-LiCl electrolyte at 373 K in the atmosphere.